Temperature field simulation and mechanical property study of directed laser depositing thin-walled Inconel 718. Issue 11 (13th September 2022) - Zhu, Lida; Ning, Jinsheng; Yuan, Cuntao
Abstract: Directed laser deposition (DLD) has become a popular forming method however it is a process with drastic temperature changes, during which the temperature accumulation effect easily causes deposition defects. Wherein the selection of the process parameters could affect the shape quality and mechanical property of the formed parts. This work investigates the distribution characteristics of the temperature field in the DLD process by finite element (FE) method and derives the temperature-time curves of special nodes which show good agreement with corresponding experimental tests. Moreover, the influence of laser power, scanning speed, and substrate initial temperature on temperature field is also studied. Based on the validation of simulation and analyses of forming defects, Inconel 718 thin-walled part with good shape was prepared by adapting the strategy of changing laser power for different layers. The formed part characterizes the finer microstructure compared with the casting part. The dendrite direction in the molten pool is mainly perpendicular to the bottom of the molten pool, and it grows epitaxially along the direction of heat flow. Besides, the mean tensile strength and elongation of the formed thin-walled part, to a certain extent, show anisotropy in the parallel and vertical direction to depositing, respectively.